Effect of Some Medicinal Tea Extracts on Some Oxidative Parameters of Sesame Oil - Hamurcu, Mehmet; Uslu, Nurhan; Al Juhaimi, Fahad; Musa Ozcan, Mehmet (Asian Journal of Chemistry, 2013)
In this study, the antioxidant activity of some medicinal tea extracts at different concentrations (0.3 and 0.5 %) on the oxidation parameters of sesame oil at 80 ºC was determined. Butylated hydroxy anisole was used as positive control in experiment. All the extracts exhibited antioxidant activity compared to butylated hydroxy anisole upto 14 days. When antioxidant effect of extract concentrations were compared with butylated hydroxy anisole, the effect of 0.5 % extract concentration was more remarkable for sesame oil upto 14 days. All of seed extracts was effective at 80 ºC in comparison with control. On the other hand, the peroxide and viscosity values during the experiment period increased. It concluded that tea extract could be used as an oxidative inhibitor agent in oil and oil products.